Open, Equitable, and Minimal: Teaching Digital Scholarly Editing North and South - Viglianti, Raffaele (2022)
In this paper, we present our preliminary reflections on whether minimal computing as a practice can extend beyond “computing done under some technological constraints” to served as a common ground between different digital humanities research dynamics in the Global North and South. We explore this question by commenting on our experience in developing and teaching an undergraduate course to students enrolled from both the University of Maryland, College Park in the United States and Universidad del Salvador in Buenos Aires, Argentina. The class was delivered for its first iteration in September–November 2020 and introduced students to digital publishing and textual scholarship of bilingual Spanish and English texts, presenting minimal computing as a shared set of values including: use of open technologies, ownership of data and code, and reduction in computing infrastructure.